Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 1 - Functions and Limits - 1.1 Four Ways to Represent a Function - 1.1 Exercises - Page 21: 27



Work Step by Step

$f(x)=4+3x-x^{2}$ Lets evaluate $\frac{f(3+h)-f(3)}{h}$ $\frac{f(3+h)-f(3)}{h}$=$\frac{4+3(3+h)-(3+h)^{2}-(4+3\times3-3^{2})}{h}$ =$\frac{4+9+3h-(9+6h+h^{2})-4}{h}$=$\frac{+9+3h-9-6h-h^{2})}{h}$=$\frac{-3h-h^{2})}{h}$= $-3-h$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.